2003
DOI: 10.1007/s10157-003-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of bucillamine-induced nephropathy in patients with rheumatoid arthritis

Abstract: In patients with proteinuria induced by treatment with bucillamine, membranous nephropathy is the most common disorder. Immediate withdrawal of bucillamine results in prompt and complete resolution of proteinuria without deterioration of renal function.Bucillamine, a disease-modifying antirheumatic drug widely prescribed in Japan, is reported to be a cause of proteinuria. However, to date, the clinical course of the nephropathy associated with the use of bucillamine has not been described in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Although the primary form is positive for only IgG4 in most cases (11), the secondary forms are varied and are often positive for multi IgG subclasses including IgG1. Cancer, antirheumatic agents such as bucillamine, and lupus are known causes of secondary MN (12)(13)(14). Localization of electron dense deposits has also been reported to be a discriminanting feature (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary form is positive for only IgG4 in most cases (11), the secondary forms are varied and are often positive for multi IgG subclasses including IgG1. Cancer, antirheumatic agents such as bucillamine, and lupus are known causes of secondary MN (12)(13)(14). Localization of electron dense deposits has also been reported to be a discriminanting feature (13).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to penicillamine, proteinuria resolves in nearly all patients after withdrawal (113). The mechanism by which penicillamine and bucillamine produce MN is unknown but may involve modification of the immune response and/or hapten formation.…”
Section: Drugs Associated With Mnmentioning
confidence: 99%
“…Clinical courses of BCL nephropathy were reported by Obayashi et al [8] and Kikuchi et al [9], who examined 10 and 13 cases of BCL nephropathy, respectively, and concluded that withdrawal of the drug results in prompt and complete resolution of proteinuria. However, both studies concluded without any statistical analysis and they did not mention about renal pathological stage.…”
Section: Discussionmentioning
confidence: 99%
“…Obayashi et al [8] reported that the interval to remission depends on BCL exposure time after onset of BCL nephropathy, from the analysis of 9 short exposed cases (mean, 2.4 ± 2.6 months of BCL exposure after onset) and 1 long exposed case (9.5 month of BCL exposure after onset). On contrast, our study showed no relationship between interval to remission and BCL exposure time after onset of BCL nephropathy.…”
Section: Discussionmentioning
confidence: 99%